2020
DOI: 10.1111/pace.13921
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of atrial fibrillation ablation in females

Abstract: Background Existing data on the effectiveness and safety of atrial fibrillation (AF) ablation in females are limited to studies of small sample size, lacking longer term follow‐up or adjustment for potential confounders. Methods A total of 6421 patients (2072 females) undergoing a first AF ablation procedure after enrollment in the Chinese Atrial Fibrillation Registry (China‐AF) study between August 2011 and December 2017 were analyzed. We evaluated the effectiveness (recurrence of documented [symptomatic or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Kaiser et al reported that women had a high risk of vascular complication, hemorrhage, and cardiac tamponade compared to men during the procedure [7]. Data from the Chinese Atrial Fibrillation Registry also showed that women had more vascular complications [8]. In the present study, we focused on in-hospital mortality, which was 0.01% and 0.03% for men and the women, respectively, that did not signi cantly change during the study period.…”
Section: Discussionmentioning
confidence: 77%
“…Kaiser et al reported that women had a high risk of vascular complication, hemorrhage, and cardiac tamponade compared to men during the procedure [7]. Data from the Chinese Atrial Fibrillation Registry also showed that women had more vascular complications [8]. In the present study, we focused on in-hospital mortality, which was 0.01% and 0.03% for men and the women, respectively, that did not signi cantly change during the study period.…”
Section: Discussionmentioning
confidence: 77%
“…Kaiser et al reported that women had a high risk of vascular complication, hemorrhage, and cardiac tamponade compared to men during the procedure [ 7 ]. Data from the Chinese Atrial Fibrillation Registry also showed that women had more vascular complications [ 8 ]. In the present study, we focused on in-hospital mortality, which was 0.01% and 0.03% for men and the women, respectively, that did not significantly change during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…CA can proceed only when no left atrial thrombi have been detected by pre-ablation transesophageal echocardiography (TEE) within 48 h. During the procedure, patients received intravenous unfractionated heparin interrupted to achieve a target activated clotting time (ACT) of 300 to 350 s. The detailed ablation strategy has been described previously. 17 Circumferential pulmonary vein isolation was achieved in all of the included patients. Left atrial linear ablation and/or complex fractionated atrial electrograms were also performed for patients with non-paroxysmal AF.…”
Section: Methodsmentioning
confidence: 99%